Identifying heating rate dependent oxidation reactions on a nickel-based superalloy using synchrotron diffraction. (December 2019) - Reynolds, T.D.; Collins, D.M.; Soor, N.K.; Street, S.R.; Warnken, N.; Mignanelli, P.M.; Hardy, M.C.; Evans, H.E.; Taylor, M.P.
Abstract: Synchrotron grazing incidence X-ray diffraction has been used to newly reveal the heating rate dependent oxidation reactions that develop on a polycrystalline nickel-based superalloy. A continuous layer of precursor oxide was shown to form during the heating stage. Their approximate growth rates, their effect on local surface compositions of the alloy substrate, and their degree of interface planarity are considered critical in determining subsequent oxidation reactions when held for extended thermal exposures. The precursor oxides were predominantly nickel or cobalt based (NiO/CoO and Co3 O4 /NiCo2 O4 ). Following the fastest heating rates (40 °C min −1 and above), the stable Cr2 O3 phase formed, inhibiting Ni or Co diffusion to the surface. At slower heating rates (10–20 °C min −1 ), no evidence of the stable Cr2 O3 was found, even after 200 h at elevated thermal exposure, instead continued growth of the precursor oxides was observed. Heating at 5 °C min −1 gave rise to an intriguing zone where sufficient precursor and favourable kinetics enabled the formation of a spinel, NiCr2 O4, surface layer. Cross sections observed with electron microscopy confirmed this to be planar and continuous. Heating at the slowest tested 2 °C min −1 contrarily gives a non-protective surface layer comprising an outwardly growing NiO/CoO precursor oxide on top of an inwardly growing mixed oxide. The quantities, interfacial morphologies of oxides of the precursor oxide grown and the possible thermodynamic reactions that lead to their formation are discussed. Graphical abstract: Image, graphical abstract